Study of the Age Hardening Behavior of Al - 4.5cu/Zrsio4 Composite in Different Quenching Media - Ashutosh (My University, 2007)
This report deals with a comparative study based on the age hardening behavior of Al- 4.5%Cu metal matrix composite reinforced with zircon sand particulates in different quenching media viz, water, oil, and salt brine solution (7%). All the samples were solutionised; quenched in water, oil, and salt solution, and aged in a vacuum oven. Vicker’s microhardness test is conducted on all samples for ageing. Optical micrographs of the as cast alloy composite indicates that the matrix of the composite has the cellular structure. Segregation of copper rich phase (CuAl2) has been found in the vicinity of particle matrix interface. Scanning electron micrographs at low magnification show uniformly distributed zircon particles throughout the matrix. Scanning electron micrographs at higher magnification shows the presence of uniformly distributed secondary phase in the alloy matrix indicating a strong continuous bond between zircon particle and the alloy matrix. Results of ageing kinetics demonstrate that the microhardness of age hardenable Al-Cu alloys depend on the rate on which the alloy is cooled after solution heat treatment. The peak hardness in oil quenched sample is attained at an early stage while water quenched sample show peak hardness at a later stage. Salt brine quenched sample shows the maximum hardness but peak hardness is in between water and oil quenched samples. Thermal cycling of the composite has been studied in different quenching media. A maximum of different heat treatment cycles are taken and microhardness of the matrix is discussed and an interesting hardness result were observed while varying quenching media.
M.Tech (Materials Science and Engg.), June 2007
Keywords: Age hardening behavior of Al-4.5%Cu/ ZrSiO4 composite, Quenching Media